2004
DOI: 10.1097/01.tp.0000100467.74330.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sinus surgery in patients with cystic fibrosis after lung transplantation: a 10-year experience

Abstract: Chronic infectious rhinosinusitis with Pseudomonas aeruginosa is common in cystic fibrosis and may result in allograft infection after lung transplantation. Sinus surgery followed by nasal care may reduce these adverse effects. Sinus surgery was performed in 37 patients with cystic fibrosis after transplantation. Bacteriology of sinus aspirates (n=771) and bronchoalveolar lavage (BAL) (n=256) was correlated with clinical data. Sinus surgery was successful in 54% and partially successful in 27% of patients. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 7 publications
6
106
0
4
Order By: Relevance
“…20 Additionally, in a series of 37 CF patients who underwent lung transplantation, aggressive sinus management led to a lower incidence of tracheobronchitis and pneumonia. 18 This suggests that aggressive management of sinus disease in the CF patient population could have a long-term benefit on the degree of bacterial transmission to the lower airway. In our series, although we did not see a change in FEV 1 %, we did observe a reduced number of hospital admissions for pulmonary exacerbations in the year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Additionally, in a series of 37 CF patients who underwent lung transplantation, aggressive sinus management led to a lower incidence of tracheobronchitis and pneumonia. 18 This suggests that aggressive management of sinus disease in the CF patient population could have a long-term benefit on the degree of bacterial transmission to the lower airway. In our series, although we did not see a change in FEV 1 %, we did observe a reduced number of hospital admissions for pulmonary exacerbations in the year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…18 As more CF patients have reached adulthood, a more aggressive treatment algorithm for CRS has emerged. Many adult CF patients have had multiple sinus surgeries-a fact highlighted by the patient group in the current study (average, 4.9).…”
Section: Discussionmentioning
confidence: 99%
“…В схожей работе эффективность синусотомии у 37 пациентов с МВ, перенесших пересадку легкого, оценена как успешная в 54% случаев, как частично успешная -в 27% [30].…”
Section: хирургическое лечениеunclassified
“…86,116 A retrospective chart review of patients who received lung transplantation and had subsequent FESS found a significant decrease in rehospitalization rates. 117 Surgery coupled with daily nasal irrigations led to a significant reduction in the incidence of tracheobronchitis as well as pneumonia and bronchiolitis obliterans syndrome in this population. 117 With conflicting evidence regarding surgical indications, it is understandable that the percentage of CF patients requiring surgical management of their disease varies considerably.…”
Section: Novel Therapeutics: Targeting the Basic Defectmentioning
confidence: 99%
“…117 Surgery coupled with daily nasal irrigations led to a significant reduction in the incidence of tracheobronchitis as well as pneumonia and bronchiolitis obliterans syndrome in this population. 117 With conflicting evidence regarding surgical indications, it is understandable that the percentage of CF patients requiring surgical management of their disease varies considerably. Virgin et al 118 used the pediatric health information services database to investigate the number patients with CF who had sinus surgery during a 3-year period at the 43 largest pediatric hospitals in the United States.…”
Section: Novel Therapeutics: Targeting the Basic Defectmentioning
confidence: 99%